PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. SINAR GALESONG PRATAMA KOTA MAKASSAR - Safira Dewi Rahmadani; Uhud Darmawan Natsir; Tenri S.P Dipoatmodjo; Romansyah Sahabuddin; Burhanuddin Burhanuddin (Lafadz Jaya Publisher, 2023)
This study aims to (1) find out how the influence of work stress on employee performance, (2) find out how the influence of motivation on employee performance, (3) find out how the influence of work stress and work motivation on employee performance of PT Sinar Galesong Pratama Makassar City. The data used in this study are primary and secondary data with a sample size of 102 respondents. This research uses a quantitative approach and is analyzed using multiple linear regression analysis methods with the help of SPSS 25 data to prove three hypotheses. The results of this study prove that Job Stress has a significant effect on employee performance, the t value of the stress variable is 3.940> t table of 3.088. That the t count of the motivation variable is 3.454> t table of 3.088. simultaneously work stress and work motivation variables on employee performance with F count of 16.326 this shows F count (16.326) > F table (1.660). Based on the results of this study, it is also known that the independent variables together or simultaneously have a significant effect on the dependent variable, namely Work Motivation of PT Sinar Galesong Pratama Makassar City. Therefore, if Employee Performance continues to be considered and improved, it will certainly improve more optimal employee performance.